Sheikh Daudal-Fatani as scholar in Malay Archipelago: overview on his writings - Mustapha, Ahmad Sharifuddin; Ali, Abdul Karim; Zainol, Nur Zainatul Nadra (Science Publishing Corporation, 2018)
This paper explores the biography of Sheikh Daud al-Fatani, one of the most famous and prolific authors among Muslims in South East Asia. He produced writings in Madhhab Shafi’i in the Malay World during the nineteenth-century. This paper discusses his background as well as the lineage of his descendants. In addition, it discusses various opinions about the date of his birth, the place he was born and the date of his death. The paper also explores his education and his teachers, and emphasizes his contribution in producing kitab and other writings that have had a huge impact on the religious education of Muslims in this region of the Malay World. To achieve the article’s objectives, content analysis method was applied to the Sheikh Daud’s writings